A New Stem Extractor with Specific Multigrip Pliers for Revision Hip Arthroplasty – A Biomechanical Investigation. Issue 5 (September 2016) - Spross, Christian; Yates, Piers J.
Introduction: It was the aim of this biomechanical study to test a new extractor with 2 specific multigrip pliers on different stem designs and to compare it to a commonly used prefabricated one (UnMod). Methods: The new extractor comprises 2 specific multigrip pliers, 1 neck-pliers and 1 shoulder-pliers. The tests were performed on a tapered and a nontapered neck stem. They were fixed in specific moulds allowing torque adjustability. The first endpoint was maximum grip with the extractors being tested up to 70 hits or failure (pliers off) in maximally fixed stems. The second endpoint was hits/attempts until stem extraction or failure (pliers off > than 5 times) in moderately fixed stems. Results: The best grip on the tapered neck was achieved by the neck-pliers without failure, whereas the others failed consistently (shoulder-pliers: mean 42.9 hits, SD: 3.5/UnMod: 40.1, SD: 5.4; p<0.01). The shoulder-pliers had the best grip on the nontapered neck withstanding more hits (11.9, SD: 1.9) than the others (neck-pliers: 4.8, SD: 1.7/UnMod: 2.8, SD 1.0; p<0.01). None of the devices failed to extract the tapered neck (UnMod best: 4, SD: 1.3). The shoulder-pliers were able to extract the nontapered neck in 60% of the tests, whereas the others failed 100%. Conclusions: The new extractor with specific pliers for neck/shoulder grip seems to be a valuable tool for stem extraction in revision hip arthroplasty. Compared to UnMod, the neck-pliers showed better grip on the tapered neck and the shoulder-pliers performed the best on the nontapered neck.